Estudos da casca de jabuticaba: extrato, emulsão e potencial entmelanogênico - Goelzer Neto, Cláudio Fernando (2024)
Melasma is a chronic hyperpigmentation of the skin that affects people's aesthetics and quality of life. The known treatment assets are not completely effective, as the lesions recur. Therefore, plant extracts capable of inhibiting the action of tyrosinase, the enzyme responsible for melanogenesis, may be a new alternative. Jabuticaba (Plynia sp.) peels are rich in phenolic compounds, such as anthocyanins, ellagic acid (EA) and others, which trigger anti-tyrosinase activity. The general objective was to produce and evaluate in vitro emulsions containing jabuticaba bark extract and azelaic acid (AA) for their anti-melanogenic potential. The jaboticaba fruits were harvested, the skin separated, dried, ground and frozen. The freeze-dried jabuticaba extract was produced with the peels. Assays were carried out to determine polyphenols, anthocyanins, flavonoids, amount of AE, antioxidant activity, solubility and cell viability/cytotoxicity of the bark and freeze-dried jabuticaba bark extract. After preparation and phytochemical characterization of the extract, four oil-in-water emulsions (NAAJ: jabuticaba extract and AA + turbo agitation; FAAJ: jabuticaba extract and AA, without turbo agitation; NAAAE: AA and AE alone, without turbo agitation; NAAA: AA isolated, without turbo agitation), were prepared and characterized in terms of average particle size, polydispersity index (PDI) and zeta potential. All samples were subjected to mushroom tyrosinase inhibition, copper ion chelation, antioxidant activity and whitening potential tests on B16F10 melanoma cells to evaluate the anti-melanogenic potential. The data were statistically evaluated. The freeze-dried jabuticaba peel extract presented the highest levels of polyphenols (817.65 mg Eq. AG/100 g ES), anthocyanins (22.82 mg Eq. Cyanidin/100 g ES), flavonoids (420.94 mg Eq. Quercetin/100 g ES) and AE (61.50 g/100 g ES) when compared to the jabuticaba peel, in addition to having a solubility in water 15 times greater than the peel (125.8 mg/mL). The antioxidant activity of the freeze-dried extract (2031.44 mg Eq. Vit C/100 g ES) was lower than that of the peel, mainly due to the time elapsed between harvesting the fruit and preparing the extract and analyzing it. The cell viability/cytotoxicity test determined that the concentrations of lyophilized jabuticaba bark extract used in cosmetic formulations should be less than 2 mg/mL. The average particle sizes of the formulations ranged from 295.20 to 630.50 nm, remaining in the nanometric range, which favors tissue action and permeation. The PDI ranged from 0.1 to 1.0. The zeta potential ranged from -6.82 to +2.02 mV. The jabuticaba bark extract stood out in the mushroom tyrosinase inhibition and antioxidant activity tests, surpassing the classic inhibitory active ingredients. The NAAA formulation proved to be more effective, with the highest percentage of tyrosinase inhibition, lowest IC50 and highest percentage of reduction in melanin synthesis in B16F10 cells. The NAAJ and FAAJ formulations stood out in the copper ion chelation test. All formulations demonstrated some anti-melanogenic potential, but to varying degrees. Despite the anti-melanogenic properties observed for the emulsions, these were inferior to the isolated jaboticaba extract, which reinforces the idea of ​​natural active ingredients as a source of whitening agents. Jaboticaba bark extract, from agro-industrial waste, stands out as an effective and sustainable alternative to treat skin hyperpigmentation. This study contributes to advances in cosmetic formulations, exploring the therapeutic potential of natural resources.